Ceria-containing mixed oxides for oxygen storage.

By developing Ce-containing mixed oxides catalysts, optimizing Ce distribution and oxygen storage capacity, the problem of insufficient catalytic performance of existing TWC is solved, and more efficient emission control and catalyst stability are achieved.

JP7664843B2Active Publication Date: 2025-04-18JOHNSON MATTHEY PLC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021551903
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-04-03
Filing Date
2020-04-01
Publication Date
2025-04-18
Estimated Expiration
2040-04-01

AI Technical Summary

Technical Problem

The existing three-way catalysts (TWCs) are inadequate in the catalytic performance and are difficult to meet new emission standards when facing increasingly stringent emission restrictions.

Method used

A new catalyst of Ce-containing mixed oxides was developed to improve the surface area and stability of the catalyst by optimizing Ce distribution and oxygen storage capacity.

Benefits of technology

It achieves more efficient CO, HC and NOx emission control, improves the oxygen storage capacity and stability of the catalyst, and maintains excellent performance under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664843000001
    Figure 0007664843000001
  • Figure 0007664843000002
    Figure 0007664843000002
  • Figure 0007664843000003
    Figure 0007664843000003
Patent Text Reader

Abstract

The present disclosure relates to Ce-containing mixed oxides, particularly Ln y Ce x M w O z wherein 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof, and Ln is one or more rare earth metals excluding Y and / or Ce, and uses of these compositions. These compositions are characterized by a uniform distribution of Ce in the lattice of the mixed oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to Ce-containing mixed oxides, particularly Ln y Ce x M w O z Compositions including those having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce; and the use of these crystalline mixed oxides as oxygen storage materials. Preferably, the compositions are characterized by the distribution of Ce in the lattice of the mixed oxide. These compositions are useful as oxygen storage compositions and in various related catalytic applications. [Background technology]

[0002] In internal combustion engines, hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NO x In gasoline engines, exhaust gases are produced that contain a variety of pollutants, including CO2, CO3, CO4, and CO5. Emissions control systems, including exhaust gas catalysts, are widely used to reduce the amount of these pollutants emitted into the atmosphere. The catalyst typically used in gasoline engine applications is the three-way catalyst (TWC). The TWC serves three main functions: (1) oxidation of CO, (2) oxidation of unburned HC, and (3) oxidation of NO2. x N 2 Give back to the community. Summary of the Invention [Problem to be solved by the invention]

[0003] TWCs, typically composed of platinum group metals (PGMs) dispersed on high surface area alumina and ceria-zirconia supports, were first introduced in the early 1980s for the aftertreatment of gasoline engines. Due to the need to meet increasingly stringent emission limits, it is desirable to identify alternative catalyst compositions with improved catalytic properties for automotive applications. Thus, there remains a need to improve and synthesize new TWC compounds with optimized catalytic properties.

[0004] In the first aspect of the present invention, Ln y Ce x M w O z A composition comprising a crystalline mixed oxide having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce; A composition is provided in which Ce is uniformly distributed throughout the lattice.

[0005] According to a second aspect of the invention, there is provided a method for preparing a crystalline mixed oxide as defined above, comprising the steps of: (a) subjecting oxide precursors of Ce and one or more of Zr, Hf, Ti, Sn, or Ge, and optionally Y, and / or one or more other rare earth metals excluding Ce, to reducing conditions to form a reduced form of a crystalline mixed oxide; (b) oxidizing the reduced form of the crystalline mixed oxide to form the crystalline mixed oxide.

[0006] In a third aspect of the present invention, there is provided a method for redistributing Ce atoms within an initial Ce-containing mixed oxide composition to provide a final Ce-containing mixed oxide composition having a Ce-Ce coordination number (CN) within 20%, within 15%, within 10%, within 5% or less of the theoretical minimum of the corresponding composition assuming perfect Ce distribution, comprising: The initial Ce-containing mixed oxide composition is Lny Ce x M w O z and having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce; The method comprises: (a) subjecting the initial mixed oxide to reducing conditions to form a reduced form of the crystalline mixed oxide; (b) oxidizing the reduced form of the crystalline mixed oxide to form the crystalline mixed oxide.

[0007] In a fourth aspect of the present invention, there is provided a method for producing a lean NOx filter for a diesel aftertreatment system, comprising: (a) a TWC or a gasoline aftertreatment system, such as a (coated) gasoline particulate filter or a diesel particulate filter or a soot filter; (b) a lean NOx filter for a diesel aftertreatment system; x traps, (c) passive NOx adsorbents (PNAs), (d) diesel oxidation catalysts (DOCs), (e) water gas shift catalysts, (f) hydrocarbon reforming catalysts, including in the case of steam reforming catalysts and / or partial oxidation catalysts, and / or (g) H 2 There is provided the use of any one of the compositions defined above in a high temperature water splitting catalyst for the production of

[0008] In a fifth aspect of the invention, the catalyst article is a TWC, a (coated) gasoline particulate filter or a diesel particulate filter or a soot filter, a lean NO filter for diesel aftertreatment. x There is provided a catalyst article comprising the composition as defined above, which is a trap, a PNA, a DOC, a water gas shift catalyst, a hydrocarbon reforming catalyst, a steam reforming catalyst, a partial oxidation catalyst, and / or a high temperature water cracking catalyst. [Brief description of the drawings]

[0009] The present application is better understood when read in conjunction with the accompanying drawings. For the purpose of illustrating the subject matter, exemplary embodiments of the subject matter are shown in the drawings. However, the subject matter of the present disclosure is not limited to the particular methods, processes, devices, and systems disclosed. Additionally, the drawings are not necessarily drawn to scale. A brief description of each of the drawings follows below.

[0010] [Figure 1] FIG. 1 shows the results of the experiment described in Example 1.

[0011] [Diagram 2] FIG. 2 shows the results of the experiment described in Example 2.

[0012] [Diagram 3] FIG. 3 shows the results of the experiment described in Example 3.

[0013] [Figure 4] FIG. 4 shows the results of the experiment described in Example 4.

[0014] [Diagram 5] FIG. 5 shows the results of the experiment described in Example 5.

[0015] [Figure 6] FIG. 6 shows the results of the experiment described in Example 6.

[0016] [Figure 7] FIG. 7 shows the results of the experiment described in Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention may be more readily understood by reference to the following description taken in conjunction with the accompanying drawings and examples, all of which form a part of this disclosure. It is to be understood that the present invention is not limited to the specific products, methods, processes, conditions, or parameters described or shown herein, and that the terminology used herein is merely for the purpose of describing specific embodiments by way of example, and is not intended to limit any claimed invention. Similarly, unless otherwise specified, any description of possible mechanisms or modes of action or reasons for improvements is merely illustrative, and is not constrained by the accuracy or inaccuracy of the proposed mechanisms or modes of action or reasons for any such improvements. It is recognized that throughout this specification, claims, and drawings, the descriptions refer to compositions and processes for making and using the compositions. That is, when the present disclosure describes or claims features or embodiments related to compositions or methods of making or using the compositions, it is to be understood that such descriptions or claims are intended to extend these features or embodiments to embodiments in each of these contexts (i.e., compositions, methods of making, and methods of using).

[0018] The present disclosure relates to compositions comprising Ce-containing crystalline mixed oxides, methods of making and using such compositions, and catalytic articles comprising these compositions.

[0019] Methods for making compositions comprising the crystalline mixed oxides described herein are further aspects of the present disclosure. Some of these methods include methods useful for preparing any of the crystalline mixed oxides described or proposed herein. In a preferred method of the present invention, the method comprises: (a) subjecting oxide precursors of Ce and one or more of Zr, Hf, Ti, Sn, or Ge, and optionally Y, and / or one or more other rare earth metals excluding Ce, to reducing conditions to form reduced forms of crystalline mixed oxides, in particular where Ce is present in the +3 oxidation state; (b) optionally maintaining the composition at a temperature allowing for (re)distribution of Ce; (c) optionally oxidizing the reduced form of the crystalline mixed oxide to form the crystalline mixed oxide.

[0020] Preferred reduction conditions are carbothermal reduction, hydrogen reduction, carbon monoxide reduction, methane reduction, or a mixture of any two or more of these reduction conditions, with carbothermal reduction and hydrogen reduction being particularly preferred.

[0021] A further preferred method includes depositing oxide precursors of Ce and one or more of Zr, Hf, Ti, Sn, or Ge, and optionally Y, and / or one or more other rare earth metals excluding Ce, onto a high surface area carbon support, followed by subjecting the supported oxide precursors to carbothermal reduction conditions.

[0022] composition The compositions of the invention include crystalline mixed oxides comprising (a) Ce, and optionally Y, and / or one or more other rare earth metals excluding Ce, and (b) one or more M elements, including Zr, Hf, Ti, Sn, or Ge, or combinations thereof. Ce is uniformly distributed throughout the lattice of the crystalline mixed oxide. In some such compositions, the lattice includes at least portions in which Ce is less uniformly distributed, such that the crystalline mixed oxide contains, in whole or in part, a local concentration of Ce. Such concentration differences can be explained in terms of Ce-Ce CN and its proximity to the theoretical minimum of the corresponding composition assuming perfect Ce distribution. In further aspects of the invention, the crystalline mixed oxides are defined in terms of their method of preparation, for example by reduction (e.g., carbothermal or hydrogen reduction) of the corresponding oxide precursors, the relative proportions of the oxide components within the range of the described compositions, the particle size and / or surface area of ​​the crystalline mixed oxide, and / or the crystalline phase and phase purity of the crystalline mixed oxide.

[0023] The composition of the present invention is y Ce x M w O zA crystalline mixed oxide having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce.

[0024] Compositions of the invention include those in which Ce is substantially uniformly distributed throughout the crystalline mixed oxide lattice, and those in which the crystalline mixed oxide lattice at least partially contains a local concentration of Ce as described elsewhere herein.

[0025] The crystalline mixed oxide may preferably be substantially free of other materials. The crystalline mixed oxide may contain dopants such as Mg, Ca and Sc to the extent that the presence of these dopants does not affect the phase properties of the crystalline material.

[0026] Preferably, the M element is or comprises Zr or Hf, or a mixture or combination thereof.

[0027] Preferably, Ln is or comprises Y, La, Nd, Pr, Gd, Sm, or a combination thereof. Particularly preferably, M is Zr and / or Hf and Ln is La, Nd, Pr, and / or Y.

[0028] The crystalline mixed oxides of the present invention can be described in terms of their porosity resulting from the aggregation or agglomeration of the crystalline mixed oxides (including, for example, mesopores and macropores). The crystalline mixed oxides may also be defined in terms of their surface area. In this latter respect, the crystalline mixed oxides have a surface area of ​​about 10 m 2 g -1 ~about 200m 2 g -1 , preferably 20m 2 g -1~ approx. 100m 2 g -1 or may be defined in terms of any subrange thereof as described elsewhere herein. The crystalline mixed oxide preferably has a crystallite size of 200 nm or less, more preferably 100 nm or less, or any other size as described elsewhere herein.

[0029] The crystalline mixed oxide may exist independently as a cubic or tetragonal phase. The crystalline phase of the crystalline mixed oxide may include some pyrochlore or monoclinic phase. However, preferably, the crystalline mixed oxide is substantially free of pyrochlore and / or monoclinic phase. As used herein, the term "pyrochlore phase" means a separate pyrochlore phase that is distinguished by a significant intensity of the 14° 2θ peak in an X-ray diffraction (XRD) pattern. As one potential measure of the ordering of the cation lattice arrangement, the crystalline mixed oxide preferably exhibits a powder X-ray diffraction (PXRD) pattern in which the ratio of the intensities of the diffraction lines at 2θ=14.5±0.5° and 2θ=29.5±1 (I 14.5 / I 29.5 ) is less than 0.02.

[0030] Preferably, the crystalline mixed oxide has a Ce-CeCN within 20%, preferably within 15%, more preferably within 10%, or even more preferably within 5% or less of the theoretical minimum of the corresponding composition assuming perfect Ce distribution.

[0031] Preferably, the crystalline mixed oxide is stable to environmental stresses, such as thermal stresses in air, where stability is measured as, for example, a crystalline mixed oxide exhibiting less than a 5% change in its Ce-Ce CN after exposing the crystalline mixed oxide to a temperature of at least 600°C in air for 2 hours.

[0032] For example, the compositions of the present invention can be used in (a) gasoline and diesel aftertreatment systems, such as TWCs or (coated) gasoline particulate filters or diesel particulate filters or soot filters; (b) lean NOx filters for diesel aftertreatment systems. x trap, (c) PNA, (d) DOC, (e) water gas shift catalyst, (f) hydrocarbon reforming catalyst, including in the case of a steam reforming catalyst and / or a partial oxidation catalyst, and / or (g) H 2 The compositions, methods of use, and systems employing such methods are all considered independent embodiments within the scope of this disclosure.

[0033] One aspect of the invention is a composition comprising a crystalline mixed oxide comprising (a) Ce, and optionally Y, and / or one or more other rare earth metals, and (b) one or more M elements, including Zr, Hf, Ti, Sn, or Ge, or combinations thereof. The inventors have found that the distribution of Ce atoms in the crystalline mixed oxide lattice has certain beneficial attributes with respect to the use of these materials, particularly for oxygen storage applications. In some embodiments, Ce is substantially uniformly distributed throughout the lattice of the crystalline mixed oxide. In other embodiments, the lattice includes at least portions in which Ce is less uniformly distributed, such that the crystalline mixed oxide contains, in whole or in part, a local concentration of Ce. An important figure of merit in such considerations is the Ce-Ce CN of the material and its proximity to the theoretical minimum of the corresponding composition assuming perfect Ce distribution. The crystalline mixed oxides can be defined in terms of their method of preparation, for example by hydrogen or carbothermal reduction of the corresponding oxides or mixed oxide precursors, the relative proportions of the oxide components, the particle size and / or surface area of ​​the crystalline mixed oxide, and / or the crystalline phase and phase purity of the crystalline mixed oxide.

[0034] Compositions contemplated within the present disclosure include (a) Ce, and optionally Y, and / or one or more other rare earth metals other than Ce; and (b) comprises a crystalline mixed oxide containing one or more M elements, which are Zr, Hf, Ti, Sn, or Ge, or a combination thereof.

[0035] The compositions discussed herein may further include one or more dopants, such as Mg, Ca, and / or Sc.

[0036] It should further be understood that any composition described herein may also include incidental impurities, such that any reference to this or any other stoichiometry is intended to take these impurities into account, and thus the mixed oxides may be considered to have (i.e., consist of) or consist essentially of the stoichiometry described herein.

[0037] As described elsewhere herein, an important feature of the compositions of the present invention is the distribution of Ce throughout the lattice of the mixed oxide. In some embodiments, the Ce is distributed uniformly throughout the lattice. The compositions may include localized concentrations of Ce. The degree of uniformity of the Ce distribution, and methods for determining the degree of uniformity of this distribution, are described elsewhere herein.

[0038] With regard to the general content of M elements, which may include one or more transition metal elements (although it is particularly preferred to include one or more of Zr, Hf, Ti, Sn, or Ge), these may generally be present such that the ratio of Ce to any one or more of the M elements varies from 1:5.7 to 1:1. In particularly preferred compositions, the M element is (i.e. consists of) or includes Zr.

[0039] With respect to the rare earth elements, including Y, the term "optionally" refers to the fact that these elements are either present or absent. Y may, but is not always, considered a lanthanide element, but for absolute clarity, is defined as such herein. The advantage of the Ln inclusion is that it improves resistance to reclustering of Ce within the structure under high temperature oxidative conditions.

[0040] In a further aspect of the invention, the composition is obtained or obtainable by reduction of a suitable precursor, either with hydrogen or other reducing gas mixtures or by carbothermal reduction, the methods and precursors being described herein.

[0041] The composition of the present invention is y Ce x M w O z A crystalline mixed oxide having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce.

[0042] As stated above, the M element may be or may include Zr or Hf, or a mixture or combination thereof. Ln may be or may include Y, La, Nd, Pr, Gd, or Sm. In preferred compositions, M is Zr or Hf and Ln is La, Nd, Pr, Gd, Sm, and / or Y.

[0043] As discussed elsewhere herein, within these frameworks, Ce is substantially uniformly distributed throughout the crystalline mixed oxide lattice. The crystalline mixed oxide may, at least in part, contain localized concentrations of Ce. The advantage of uniformly distributing Ce within the structure compared to localized clustering of Ce is that the oxygen storage capacity of the mixed oxide is improved. Furthermore, during certain stresses encountered during the use of these materials, Ce atoms may move within the lattice by various mechanisms. In part, this is a result of the Ce atoms finding it increasingly difficult to congregate into locally concentrated "islands". By maximizing the initial distribution of these Ce atoms within the lattice, a lifetime of optimal performance is maintained.

[0044] The degree of ordering (or "uniformity" of distribution) can be quantified in terms of the Ce-Ce (or Ce-O-Ce) coordination number within the crystalline mixed oxide, and in particular in terms of the proximity to a theoretically perfect distribution. This represents a measure of the degree of ordering (or mixing) of Ce within the cation sublattice of the structure. In a perfectly mixed lattice (e.g., a binary mixed oxide), Ce should have a minimum number of Ce-O-Ce neighbors and conversely a maximum number of Ce-OM element neighbors. An increase above this minimum represents incomplete mixing (or nanoclustering of Ce within the structure).

[0045] The theoretical minimum Ce-O-Ce value for a given composition is 2 It is determined by referring to CeO 2 is a face-centered cubic structure, where each Ce has 8 O neighbors and 12 next neighbors Ce. Thus, for example, fully mixed Ce 0.5 Zr 0.5 O 2 In the case of the structure, half of the Ce in the next adjacent atoms are replaced by Zr, so the Ce-Ce CN is 6 (similarly, Ln y Ce x M w O zIn the structure described herein in terms of x=0.5, these conditions are still met, even though the next neighbor is an Ln or M element). Thus, when the Ce-Ce CN is 7.8, the Ce-Zr CN is only 4.2, thus representing an incompletely mixed lattice. The local structure of this material contains nanodomains of Ce-rich and Zr-rich regions within individual crystallites. This incomplete mixing is difficult to extract from the XRD powder pattern. The only useful feature is the extra superlattice reflections that arise from the ordered structure, since the Ce and Zr cation sublattices develop an ordered interpenetrating arrangement, resulting in extra diffraction reflections. Furthermore, ordering can also be measured by a combination of X-ray diffraction and X-ray absorption spectroscopy (specifically, Extended X-ray Absorption Fine Structure (EXAFS) or X-ray scattering using Pair Distribution Function (PDF) analysis). Thus, this ordering can be defined in terms of at least one of these methods.

[0046] Preferably, the crystalline mixed oxide has a Ce-CeCN as described herein that is within 20%, 18%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, or 1% of the theoretical minimum of the corresponding composition assuming perfect Ce distribution. This coordination can be measured macroscopically or in specific regions of the crystalline mixed oxide.

[0047] For some crystalline mixed oxides described herein, the stability of the crystalline mixed oxide may be defined in terms of the change in CN after the mixed oxide is exposed to a particular thermal, reductive, and / or oxidative stress. Thus, some preferred compositions include crystalline mixed oxides that exhibit a change in Ce-Ce CN of less than 20%, less than 15%, less than 10%, less than 8%, less than 6%, less than 5%, or less than 4% compared to the original Ce-Ce CN after exposure in air to temperatures ranging from 400 to 1200°C, preferably 500 to 1100°C, for 1 to 10 hours.

[0048] Particularly preferred compositions, for example, exhibit less than 5% change after exposure in air to a temperature in the range of 600°C to 800°C for 4 hours, or less than 8% change after exposure in air to a temperature in the range of 400°C to 900°C for 5 hours.

[0049] Nanoclustering or even macroclustering occurs in Ce-containing mixed oxide materials prepared by grinding, mixing, and sintering the component oxides. Such methods inevitably result in incomplete, or at least not complete or "perfect" mixing, resulting in localized regions of residual ceria with high levels of Ce-O-Ce neighbors. Ce-containing mixed oxide materials can also be made by other routes, such as co-precipitation, but again, localized regions of incomplete mixing can occur unless special precautions are taken in the synthesis. For example, if the Ce content is 50 mol% or less and the Ce is uniformly distributed in the lattice, theoretically, less than half of the cations adjacent to each Ce atom should be Ce. With careful control of the preparation conditions, such samples can be single-phase as determined by X-ray diffraction, but most often contain regions of incomplete mixing and the Ce is more or less clustered. For some specific Ce-containing mixed oxide chemical compositions, the complete dispersion of Ce within the structure is manifested as a very high degree of cation sublattice order that can be seen through the appearance of weak superlattice lines in the XRD. However, in general, advanced characterization sensitive to the local structure is required to determine the degree of Ce-O-Ce adjacency and measure the Ce distribution within the structure.

[0050] The crystalline mixed oxides of the compositions of the present invention are typically present in tetragonal phase, cubic phase, or combinations thereof. Within these compositions, the mixed oxides preferably contain less than 10%, less than 5%, less than 3%, less than 2%, less than 1%, or less than 0.5% of pyrochlore phase. Preferably, the crystalline mixed oxides are substantially or essentially free of pyrochlore phase (e.g., pyrochlore phase is not detected by PXRD analysis).

[0051] In some preferred compositions, the compositions are characterized in terms of the ratio of the diffraction line intensities of the crystalline mixed oxides. This provides insight into the phase purity and nature of the order of the crystal lattice. In some embodiments, the mixed oxides exhibit diffraction peaks in their PXRD patterns at 2θ=14.5±0.5° and 2θ=29.5±1°. Recognizing the potential influence of experimental artifacts (e.g., sample preparation, sample packing, crystallite size, etc.) when using the peak intensities, the inventors have discovered that one useful figure of merit is the ratio of these two peaks. The ratio of the reflections refers to the proportion of order in the cation lattice arrangement. The reflection at 14.5±0.5° indicates the formation of a superlattice arrangement of cations within the overall cation sublattice. The greater the intensity of this reflection compared to the reflection at 29.5±1°, the greater the degree of ordering of the structure. In certain embodiments, the ratio of the reflections at 2θ=14.5±0.5° (I 14.5 ) and 2θ=29.5±1°(I 29.5 The ratio of the diffracted line intensities at 14.5 / I 29.5 ) is less than 0.1, less than 0.08, less than 0.07, less than 0.06, less than 0.05, less than 0.04, less than 0.03, less than 0.02, less than 0.01, or less than 0.005. Preferably, this ratio is less than 0.02, particularly preferably less than 0.01, or substantially zero. Other patents relating to bulk ordered CeZr materials impose a minimum requirement on this ratio as an indication that the bulk structure of the material is sufficiently ordered.

[0052] The crystalline mixed oxides of the compositions described herein typically have a crystallite size ranging from about 1 nm to about 250 nm, preferably from about 1 nm to about 100 nm, for example, from about 10 nm to about 25 nm. The crystallite size is estimated from the line broadening of the reflections in the XRD pattern (using Reitveld analysis). This approach measures the repeat distance of unit cells in a particular direction of the reflection lattice plane. These distances can also be ascertained by TEM, but the use of TEM as the primary measurement approach is less preferred due to poor particle count statistics.

[0053] These nanoscale crystallites may also aggregate or agglomerate to larger particle sizes. Typically in these cases, the aggregates or agglomerates are disordered in macrostructure, at least with respect to crystallite orientation, with mesoporous or macroporous pores permeating the aggregates. Preferably, the particles of these crystalline mixed oxides, either as crystallites or aggregates, are larger than about 5 mm. 2 g -1 ~about 200m 2 g -1 , preferably about 10 m 2 g -1 ~ approx. 100m 2 g -1 These surface areas are most conveniently measured by inert gas (e.g., nitrogen or argon) porosimetry and analyzed using the BET equation. When specific values ​​are quoted herein, they are measured on a 3Flex surface property analyzer (Micromeritics) at 77 K in N 2 can be seen as being obtained using

[0054] Preferably, the particles of these crystalline mixed oxides, either as crystallites or aggregates, are less than about 10 μm. 2 g -1 It has a surface area of ​​more than 10 m 2 g -1The advantage of these particles is that there are several support sites available for anchoring transition metal or other element promoters (e.g., Pt, Pd, or Rh) to access the oxygen storage function or to catalyze the oxygen storage function, i.e., improving the rate of oxygen transfer in and out of the structure, thus leading to improved performance, or other catalytic functions.

[0055] The compositions described herein may also further comprise a transition metal or transition metal oxide catalyst distributed on the surface of the crystalline mixed oxide and / or within the pores of the aggregated or agglomerated crystalline mixed oxide particles. Although the full scope of the terms transition metal and / or transition metal oxide are defined elsewhere herein, such materials preferably comprise at least one metal and / or oxide thereof (including physical mixtures or alloys) of at least one of Cr, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, or Zn. Such catalysts may be deposited chemically or by vapor deposition techniques, as known to those skilled in the art.

[0056] Method for making the composition While the present disclosure up to this point has focused on compositions, further aspects of the present invention also include methods of making the crystalline mixed oxides as described herein.

[0057] In some Ce-containing mixed oxides, the formation of Ce in the +3 oxidation state facilitates easy and uniform distribution of Ce by migration throughout the lattice of the crystalline mixed oxide. These principles can also be used to prepare Ce-containing crystalline mixed oxides in which Ce is substantially uniformly dispersed from the oxide precursor into the mixed oxide lattice, or to redistribute Ce within an existing crystal structure. As shown in the examples, the formation of certain highly ordered phases or reduction heat treatment of preformed single-phase mixed oxides, e.g., Ce, 0.5 Zr 0.5 O 2 Through treatment with hydrogen at temperatures above 900 °C, Ce is prepared and locked in the +3 oxidation state. 2Such reduction heat treatment by H is more difficult to control and can lead to a significant collapse of the surface area. An improvement to this disclosure further covers the formation of higher surface area ordered structures by co-precipitation of Ce mixed oxides onto high surface area carbon supports. A reduction heat treatment can then be carried out (H 2 or preferably in a carbothermal mode, where a portion of the carbon support acts as a reducing agent, so that the surface area of ​​the mixed oxide is not collapsed. The carbon support can then be removed by treatment in air at a temperature that does not cause significant sintering.

[0058] In the context of this disclosure, one aspect of the invention is then a method for redistributing Ce atoms within an initial Ce-containing mixed oxide composition to provide a final Ce-containing mixed oxide composition having a Ce-Ce CN within 20%, within 15%, within 10%, within 5% or less of the theoretical minimum of the corresponding composition assuming perfect Ce distribution, comprising: The initial Ce-containing mixed oxides are (a) Ce, and optionally Y, and / or one or more other rare earth metals other than Ce; and (b) containing one or more M elements that are Zr, Hf, Ti, Sn, or Ge, or a combination thereof; The method comprises: (a) subjecting the initial mixed oxide to reducing conditions to form a reduced form of the crystalline mixed oxide; (b) oxidizing the reduced form of the crystalline mixed oxide to form a final Ce-containing crystalline mixed oxide.

[0059] In such a method, the elemental composition of the Ce-containing mixed oxide before and after treatment is essentially the same, and the only difference between the initial and final is the distribution of Ce within the lattice, which is more uniformly distributed after treatment than before (Ce-Ce CN is closer to the theoretical value). The degree of uniformity of Ce distribution, and methods for determining the degree of uniformity of this distribution, are described elsewhere herein.

[0060] In a preferred method of the present invention, the Ce-containing mixed oxide composition comprises Ln yCe x M w O z having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce.

[0061] Preferably, the reducing conditions comprise treating the initial mixed oxide with hydrogen at elevated temperature.In another preferred method of the invention, the reducing conditions comprise subjecting the initial crystalline mixed oxide to carbothermal reducing conditions.

[0062] A further aspect of the present invention is a method for making a crystalline mixed oxide as described above, comprising the steps of: (a) subjecting oxide precursors of Ce and one or more of Zr, Hf, Ti, Sn, or Ge, and optionally Y, and / or one or more other rare earth metals excluding Ce, to reducing conditions to form a reduced form of a crystalline mixed oxide; (b) optionally oxidizing the reduced form of the crystalline mixed oxide to form the crystalline mixed oxide.

[0063] Preferred reduction conditions are carbothermal reduction, hydrogen reduction, carbon monoxide reduction, methane reduction, or a mixture of any two or more of these reduction conditions, with carbothermal reduction and hydrogen reduction being particularly preferred.

[0064] In a preferred method, oxide precursors of Ce and one or more of Zr, Hf, Ti, Sn, or Ge, and optionally Y, and / or one or more other rare earth metals excluding Ce, are deposited on a high surface carbon support and then the supported oxide precursors are subjected to reducing conditions.

[0065] As described herein, carbothermal reduction is carried out using a gas phase reducing agent (H 2It relies on the use of carbon as a reducing agent rather than a cation (such as Cr or CO). The mixed oxide precursors are deposited on a suitable high surface carbon support, allowing good contact between the carbon and the oxide precursor particles. Treatment of the resulting mixture under inert conditions crystallizes and reduces the mixed oxide to give a supported reduced composition (which is still an oxide, but just in reduced form). It is most easily done by precipitating the individual components together as amorphous hydrous oxides / hydroxides / carbonates on carbon, for example by co-precipitation of a soluble salt with a base. The carbon reduces Ce from 4+ to 3+, and the Ce 3+ It has been shown in the literature that this is a convenient route to ordering the composition, since the mismatch in ionic radius size between Ce and the major M element cations promotes ordering. Treatment of the resulting material to moderate temperatures in air or other oxygen-containing atmospheres removes the carbon support by combustion, and the Ce is freed while maintaining the ordered or reordered structure. 3+ is oxidized to Ce 4+ Carbon is also essential to keep the particles separated during the reduction process to preserve surface area (and limit crystallite size growth due to thermal sintering).

[0066] Carbon heat treatment is not easily applicable to preformed crystalline oxide materials, especially commercially available oxide materials with larger crystallite sizes, because it is difficult to disperse the already crystalline material on carbon. Amorphous / hydrous metal oxides or carbonates are useful precursors.

[0067] Suitable carbon sources include preformed amorphous carbon powders, including activated carbon powder, carbon black, carbon soot, and lamp black, and / or can be derived from commercial sources or from polymers that are decomposed or pyrolyzed under non-oxidizing conditions to form carbonaceous materials. Highly dispersed amorphous materials favor the intimate mixing required, or at least preferred, for these syntheses. A particularly preferred carbon source is high purity carbon, since it may be desirable to minimize the amount of inorganic residues in the final crystalline mixed oxide material. Examples of this type of high purity carbon include acetylene black and highly conductive black (e.g., KETJENBLACK).

[0068] Typical sources of crystalline oxide precursors of Ce, M elements, or Ln metals include alkoxides (e.g., C 1-6 alkoxides), hydroxides, hydrous oxides, hydrogels, fumed or colloidal oxides, or combinations thereof. Additionally, any oxide salt of these metals or elements, such as those known for use in sol-gel synthesis, including β-diketonates (e.g., acetylacetonate, or "acac"), alkyl-substituted β-diketonates (e.g., 2,2,6,6-tetramethyl-3,5-heptanoate, etc.), carbonates, carboxylates (e.g., acetates, propionates, 2-ethylhexanoates, octanoates), halides, hydroxides, nitrates, oxalates, and / or sulfates, may serve as suitable precursors, although the use of precursors that do not contain halides or sulfur is preferred. Similarly, more expensive but useful precursors for atomic layer deposition, such as dialkylaminoalkoxides (e.g., dimethylaminoethoxide), optionally substituted formamides, or dialkyl or diarylamides (-NR 2 , R is alkyl, such as methyl, ethyl, (iso)propyl, etc., or aryl, such as phenyl) are also useful in this regard.

[0069] For the avoidance of doubt, each of the elements or metals described herein (including at least Ce, Zr, Hf, Ti, Sn, Ge, Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, or any transition metal material) and any of the aforementioned precursor types, or combinations thereof, may be present in the oxide precursors or crystalline oxide precursors described herein as being used or useful.

[0070] The carbon and the (crystalline) oxide precursor can be intimately mixed by physical methods, or the carbon can be mixed with the (crystalline) oxide precursor source during the formation of the precursor (e.g. trapped in the sol-gel lattice during sol-gel processing of the (crystalline) oxide precursor). Alternatively, the (crystalline) oxide precursor can be sprayed or otherwise deposited onto the carbon source.

[0071] Typical conditions used for carbothermal reduction include heating (and holding) intimately mixed (crystalline) oxide precursors and carbon in a non-oxidizing atmosphere at temperatures in the range of 350° C. to 1100° C., preferably 350° C. to 850° C. The treatment regime must be sufficient to reduce fully oxidized forms of elements or metals to lower valence state materials, but not to reduce either to their elemental or carbide forms.

[0072] The resulting reduced form of the crystalline mixed oxide is oxidized by a suitable chemical method to form the crystalline mixed oxide. Such suitable chemical methods can include, for example, treatment at elevated temperature in the presence of oxygen and / or organic or hydrogen peroxide materials for a time and under conditions sufficient to form the crystalline mixed oxide. The oxidation can be carried out at a temperature in the range of 350°C to 1100°C, preferably in the range of 350°C to 850°C. Preferably, the components of the crystalline mixed oxide are fully oxidized and have particle sizes and characteristics as described elsewhere herein, and / or the carbon is fully combusted.

[0073] Use of the composition The present disclosure also contemplates within its scope the use of any one of the compositions described herein in any method, catalyst, or system used in the conversions described herein. Ce / Zr systems are known to be useful as oxygen storage systems, and it is believed that the compositions defined in the present invention are useful and offer certain advantages over previously reported Ce / Zr systems in this regard. Such mixed oxide systems are also useful more generally in the context of oxidation, reduction, reforming, aqueous splitting, and water gas shift catalysis, both by themselves and in the context of large-scale systems. Each of these catalyst forms and systems is considered a separate embodiment of the present disclosure.

[0074] These capabilities are also within the scope of this disclosure as: (a) TWC or gasoline or diesel aftertreatment systems such as (coated) gasoline or diesel particulate filters and / or soot filters; (b) lean NO for diesel aftertreatment systems; x trap, (c) PNA, (d) DOC, (e) water gas shift catalyst, (f) hydrocarbon reforming catalyst, including in the case of a steam reforming catalyst and / or a partial oxidation catalyst, and / or (g) H 2 This provides the basis for including applications such as high temperature water splitting catalysts to produce

[0075] The use of the compositions of the present invention in TWCs as described above is particularly preferred.

[0076] Oxygen storage compositions and materials Celia (CeO 2Ceria-based oxygen storage component materials are important components in treating emissions from engines. Ceria is also used as a support for palladium (Pd), platinum (Pt), and rhodium (Rh) in treating hydrocarbon and NOx emissions from gasoline and diesel vehicles. One of the important properties of ceria-based OSC materials is the ability of ceria to switch between the +4 and +3 oxidation states. This redox property makes ceria-based materials useful in a variety of emissions treatment applications. Thus, the compositions of the present disclosure are useful in these applications.

[0077] Three-way catalyst (TWC) article For reasons well known in the art, TWCs have been developed to incorporate components that store oxygen during lean periods of the operating cycle and release oxygen during rich periods of the operating cycle, thereby extending the effective operating period. For this purpose, ceria-based (e.g., ceria-zirconia mixed oxide) materials are used as the oxygen storage component (OSC) in the majority of current commercially available TWCs.

[0078] The compositions described herein are well suited and offer significant advantages over other systems used for this purpose, in particular the uniformity of distribution of Ce in the mixed oxide compositions described herein provides a level of stability and oxygen storage capacity not recognized or achieved by other materials that do not include this feature.

[0079] Thus, one aspect of the present invention relates to a catalytic article for treating exhaust gas comprising at least the crystalline mixed oxide composition disclosed herein. Such catalytic article may also comprise a substrate and a catalytic region on the substrate, the catalytic region comprising a first platinum group metal (PGM) component and a composition comprising any one of the crystalline mixed oxides described herein that functions as an OSC material. The catalytic article may also comprise an inorganic oxide support. Additional aspects of the present invention also include exhaust systems for internal combustion engines. Still further aspects of the present invention include methods for treating exhaust gas from internal combustion engines, particularly exhaust gas from gasoline engines. The method comprises contacting the exhaust gas with the catalytic article of the present invention, e.g., the TWC article.

[0080] In some preferred catalytic articles described herein, the crystalline mixed oxides of the present disclosure are ceria, zirconia, and La. 2 O 3 , Nd 2 O 3 , Y 2 O 3 ,Pr 6 O 11 The present invention includes mixed oxides containing one or more of the following:

[0081] In the context of this use, the first PGM is preferably palladium, platinum, rhodium, and mixtures thereof. More preferably, the first PGM is palladium. The catalytic zone may further comprise a second PGM component, which may be palladium, platinum, rhodium, and mixtures thereof. Particularly preferably, when the first PGM component is palladium, the second PGM component is rhodium. The catalytic zone may further comprise a third PGM component, which may be palladium, platinum, rhodium, and mixtures thereof. Thus, the catalytic zone may comprise a trimetallic PGM component, such as PtPdRh. Preferably, the catalytic zone is essentially free of PGM metals other than the palladium component.

[0082] Also within this context, the OSC material may range from 20 to 80 wt %, based on the total weight of the catalyst region.

[0083] The catalytic region in this context may contain further components known to those skilled in the art. For example, the composition of the present invention may further comprise at least one binder and / or at least one surfactant. When a binder is present, a dispersible alumina binder is preferred.

[0084] Also, in this context, the substrate may be a metal or ceramic substrate. Preferably, the substrate is a flow-through monolith or a filter monolith. Suitable materials for forming the monolith substrate include ceramic-like materials such as cordierite, silicon carbide, silicon nitride, zirconia, mullite, spodumene, alumina-silica magnesia or zirconium silicate, or porous refractory metals. Such materials and their use in the manufacture of porous monolith substrates are well known in the art.

[0085] Gasoline and diesel particulate filters and catalyzed soot filters Compression ignition internal combustion engines are also known to generate particulate matter due to incomplete combustion of the fuel used therein, as well as particulate traps to trap the particulate matter in the exhaust gas in the exhaust passage. The purpose of these traps or filters is to suppress the amount of particulate matter emitted into the atmosphere in the context of exhaust purification systems. Such filter systems often include structures that include mixed oxides such as alumina, silica-titania, titania-zirconia, silica-zirconia, silica-gallium oxide, titania-alumina, silica-yttrium oxide, alumina-zirconia, silica-lanthanum oxide, titania-cadmium oxide, titania-tin oxide, titania-zinc oxide, zinc oxide-silica, and zinc oxide-cadmium oxide. Thus, the present compositions and mixed oxide systems are particularly suitable for this application, and filters including the compositions described herein are also considered part of the present disclosure.

[0086] When used in the context of the TWC system discussed above, in exhaust systems that include both features, the particulate filter may be located either upstream or downstream of the three-way catalyst. The TWC may additionally or alternatively reside on the particulate filter.

[0087] Diesel Oxidation Catalyst Both diesel and gasoline engines emit at least four pollutants that are regulated by intergovernmental organizations around the world: CO, unburned HC, and NO. x Engines produce exhaust gases, which typically contain polluting gases (PGMs) and particulate matter (PM) to varying degrees. Emission standards for both types of engines, whether stationary or mobile (e.g., vehicular engines), are becoming increasingly stringent. There is a need to provide improved, cost-effective catalysts and exhaust systems that meet these standards.

[0088] Oxidation catalysts, such as diesel oxidation catalysts (DOCs), typically oxidize CO and HC in the exhaust gas produced by diesel engines. Diesel oxidation catalysts convert a portion of the nitric oxide (NO) present in the exhaust gas into nitrogen dioxide (NO 2 ) can also be oxidized to NO 2 Although NO itself is a pollutant, 2 It may be beneficial to convert the generated NO 2 can be used, for example, to regenerate PM trapped by a downstream diesel particulate filter (DPF) or downstream catalyzed soot filter (CSF). 2 is the amount of NO in the exhaust gas from the outlet of the oxidation catalyst compared to the inlet exhaust gas. 2b :NO ratio. This increased ratio can be beneficial for exhaust systems that include downstream selective catalytic reduction (SCR) catalysts or selective catalytic reduction filter (SCRF™) catalysts. NO in the exhaust gases generated directly by diesel engines 2 The ratio of NO to CO may be too low for optimal SCR or SCRF catalyst performance.

[0089] At least in this context, embodiments include those oxidation catalysts that include one or more transition metal catalysts, preferably platinum group catalysts. In some embodiments, the catalytic metals independently include any one or more of Pd, Pt, Rh, gold (Au), silver (Ag), iridium (Ir), ruthenium (Ru), and mixtures of two or more thereof.

[0090] These catalysts can be incorporated into exhaust systems, in which case the exhaust system and the stationary or mobile (e.g., vehicular) exhaust generators that include the exhaust system are considered to form part of the present disclosure. It should also be understood that the use of these materials as oxidation catalysts is not limited to use in diesel systems, or even internal combustion systems, but also in other chemical process-oriented systems such as the destruction of volatile organic compounds (VOCs), the treatment and clean-up of HCs, water-gas shift (WGS) reactions, or, for example, the partial selective oxidation of CO in syngas.

[0091] Lean NO for diesel aftertreatment x trap Inline No. x The use of storage units is often referred to as lean NOx traps, but is now more commonly referred to as NO x Trap or NO x Absorption catalyst (NO x These are commonly known as NOx absorber catalysts (NACs) and are best known in the exhaust gas aftertreatment systems of lean-burn internal combustion engines. Perhaps the earliest published patent was Toyota's European Patent No. 0560991, which describes the use of materials such as barium oxide and platinum to react with NOx to form nitrates. x By incorporating a conversion catalyst, NO x The authors describe how a storage unit can be constructed. The trap is periodically regenerated by adjusting the air-fuel ratio (commonly called "lambda" or λ) to stoichiometric (λ=1) or rich (λ>1), so that NO x is released and simultaneously reduced to nitrogen gas by contact with the catalyst.

[0092] Conventional NO x Trap is NO x It is constructed by depositing the trap component (eg, an alkaline earth or rare earth material such as barium, neodymium, or lanthanum), and optionally the OSC and catalytic components, onto a honeycomb-shaped flow-through substrate monolith.

[0093] The composition defined herein is a lean NO x TRAP (lean NO x trap, LNT), e.g., lean NO for diesel aftertreatment x It may be useful as an oxygen storage component in a trap.

[0094] definition In this disclosure, unless expressly stated otherwise, the singular forms "a," "an," and "the" include plural references and a reference to any particular numerical value includes at least that particular value. Thus, for example, a reference to a "material" is a reference to at least one of such materials and equivalents thereof known to those skilled in the art, and so forth.

[0095] When values ​​are expressed as approximations by using the descriptor "about", it will be understood that the particular value forms another embodiment. In general, the use of the term "about" indicates an approximation that may vary depending on the desired properties sought to be obtained by the disclosed subject matter and should be interpreted in the particular context in which it is used based on its function. Those skilled in the art will be able to interpret this as they do routinely. In some cases, the number of significant figures used for a particular value may be one non-limiting way of determining the scope of the word "about". In other cases, the gradations used in a series of values ​​can be used to determine the intended range available to the term "about" for each value. When present, all ranges are inclusive and combinable. That is, reference to values ​​stated in a range includes every value within that range.

[0096] For clarity, it should be understood that certain features of the invention described herein in the context of separate embodiments may also be provided in combination in a single embodiment. That is, unless expressly incompatible or specifically excluded, each individual embodiment is considered to be combinable with any other embodiment, and such combination is considered to be another embodiment. Conversely, for brevity, various features of the invention that are described in the context of a single embodiment may also be provided individually or in any subcombination. Finally, while an embodiment may be described as part of a series of steps or as part of a more general structure, each step may also be considered to be an independent embodiment in itself and combinable with other steps.

[0097] The transitional terms "comprising," "consisting essentially of," and "consisting" are intended to include their generally accepted meanings in patent terminology, i.e., (i) "comprising" is synonymous with "including," "containing," or "characterized by" and is inclusive or open-ended and does not exclude additional, unrecited elements or method or process steps; (ii) "consisting of" excludes any element, step, or ingredient not specified in the claim; and (iii) "consisting essentially of" limits the scope of the claim to the specified materials or steps and those "which do not materially affect the basic and novel characteristics" of the claimed invention. The embodiments described in terms of the phrase "comprising" (or its equivalents) also provide, as embodiments, the embodiments described independently in terms of "consisting of" and "consisting essentially of". For those embodiments provided in terms of "consisting essentially of", the fundamental and novel property(ies) of the process is the ability of any compositional changes within the crystalline mixed oxide to maintain its specified topology and to maintain the Ce-Ce coordination number within the crystalline mixed oxide at the described or claimed level.

[0098] When a list is presented, unless otherwise stated, each individual element of that list, and all combinations of that list, are to be understood as separate embodiments. For example, a list of embodiments presented as "A, B, or C" should be interpreted to include the embodiments "A", "B", "C", "A or B", "A or C", "B or C", or "A, B, or C". As a further example, a list of "Pt, Pd, and / or Rh" includes the individual embodiments "Pt", "Pd", "Rh", "Pt and / or Pd", "Pt and / or Rh", "Pd and / or Rh", and "Pt, Pd, and / or Rh". Similarly, the use of the symbols "≦" and "≧" refers to a range in which the endpoint values are included within the range. However, subsets of these ranges may also include those in which one or both of the endpoint values are excluded. For example, the embodiment "0.15≦x≦0.5" refers to a range defined such that the range includes the endpoints 0.15 and 0.5. Separate and independent embodiments include those in which the range may be defined as "0.15<x≦0.5" or "0.15≦x<0.5" or "0.15<x<0.5".

[0099] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention, but representative exemplary methods and materials are described herein.

[0100] As understood by one of ordinary skill in the relevant art, throughout this specification, words should be given their ordinary meaning. However, to avoid misunderstanding, the meaning of specific terms is specifically defined or clarified.

[0101] The terms "Ce-Ce coordination number" and "Ce-O-Ce coordination number" are used interchangeably to refer to the average number of Ce atoms adjacent to (with O intervening) any other Ce atom within the mixed oxide lattice.

[0102] Terms such as "halo" and "halogen" are used in the conventional sense to refer to a chloro, bromo, fluoro, or iodo substituent.

[0103] Unless otherwise specified, the term "isolated" means physically separated from other components such as free of solvent or other impurities, and additional embodiments include those in which the compound is substantially the only solute in a solvent or solvent fraction and is analytically separated in such a liquid or gas chromatographic phase.

[0104] The term "mixed oxide" as used herein generally refers to a mixture of oxides in a single phase, as conventionally known in the art. The term "complex oxide" as used herein generally refers to a composition of oxides having two or more phases, as conventionally known in the art.

[0105] "Optional" or "optionally" means that the subsequently described circumstance may or may not occur, and thus the description includes embodiments in which the circumstance occurs and those in which it does not occur. For example, the term "optionally Y and / or one or more rare earth metals other than Ce" means that Y and / or one or more rare earth metals may or may not be present in the crystalline mixed oxide, and the description includes compositions in which these materials are present and those in which these materials are absent. Similarly, the phrase "optionally isolated" means that the target material may or may not be separated from other materials used or produced in the method, and thus the description includes separate embodiments in which the target molecule or other materials are separated and in which the target material is not separated, such that subsequent steps are performed on the isolated product or on the product produced in situ.

[0106] As used herein, the acronym "PGM" refers to "platinum group metals." The term "platinum group metals" generally refers to Ru, Rh, Pd, Os, Ir, or Pt, preferably Ru, Rh, Pd, Ir, or Pt. The term "PGM" preferably refers to at least one of Rh, Pt, and / or Pd.

[0107] The terms "separating" or "separated" have their ordinary meaning as would be understood by one of ordinary skill in the art insofar as they refer to separating or isolating a product material from other starting materials or co-products or side-products (impurities) associated with the reaction conditions that produce that material. Thus, it implies that one of ordinary skill in the art at least recognizes the presence of the product and takes specific action to separate or isolate it. Absolute purity, although preferred, is not essential, since the material may contain small amounts of impurities and the separated or isolated material may contain residual solvent or may be dissolved in the solvent used in the reaction or subsequent purification of the material.

[0108] As used herein, the term "crystalline mixed oxide" is a crystalline structure that includes a substantially uniform macroscopic composition, whether or not the Ce atoms are uniformly distributed throughout.

[0109] Consistent with its traditional meaning, the term "transition metal" or "transition metal oxide" refers to metals or oxides of elements in the d-block of the periodic table, including groups 3 through 12 of the periodic table. Such elements include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, La, Hf, Ta, W, Re, Os, Ir, Pt, and Au.

[0110] Also, as used herein, consistent with its traditional meaning, the term "rare earth metal" refers to elements considered to be within the lanthanide and actinide series, in particular cerium (Ce), dysprosium (Dy), erbium (Er), europium (Eu), gadolinium (Gd), holmium (Ho), lanthanum (La), lutetium (Lu), neodymium (Nd), praseodymium (Pr), promethium (Pm), samarium (Sm), scandium (Sc), terbium (Tb), thulium (Tm), and ytterbium (Yb). In some definitions, yttrium (Y) is also considered a rare earth element, but to avoid any doubt as to its possible inclusion in this category herein, it is specifically mentioned throughout in this regard.

[0111] As used herein, the term "substantially free" as used herein with respect to a material typically means that the material is present in a small amount, e.g., 5% by weight or less, preferably 2% by weight or less, more preferably 1% by weight or less, in the context of a composition. The term "substantially free" encompasses the term "free". The term "essentially free" as used herein means that the material is present in an even smaller amount, e.g., 1% by weight or less, preferably 0.5% by weight or less, more preferably 0.1% by weight or less. The term "essentially free" encompasses the term "free".

[0112] As used herein, any reference to an amount of dopant expressed as weight percent, particularly a total amount, refers to the weight of the support material or refractory metal oxide thereof.

[0113] The following list of specific embodiments is intended to complement, rather than replace or supplant, the foregoing description.

[0114] Embodiment 1. (a) Ce, and optionally Y, and / or one or more other rare earth metals other than Ce; and (b) A composition comprising a crystalline mixed oxide containing one or more M elements, where M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof.

[0115] In some aspects of this embodiment, the Ce is uniformly distributed throughout the lattice. In other aspects, the composition includes a localized concentration of Ce. The degree of uniformity of the Ce distribution, and methods for determining the degree of uniformity of this distribution, are described elsewhere herein.

[0116] It should be understood that each M element or combination thereof provides an independent aspect of this embodiment. In a particular aspect, the M element is or includes Zr.

[0117] In independent aspects of this embodiment, Y and / or one or more rare earth metals other than Ce are present or absent.

[0118] In one aspect of this embodiment, each of Ce, one or more M elements, Y, and one or more rare earth metals are in their fully oxidized valence states. In an additional independent aspect of this embodiment, one or more of these metals or elements are present in the composition in a partially oxidized state (i.e., not fully oxidized).

[0119] In some independent aspects of this embodiment, the compositions are obtained or obtainable by reduction (e.g., carbothermal or hydrogen reduction) of suitable precursors, the methods and precursors being described herein, i.e., the use of such methods, and the compositions derived or derivable therefrom, are independent aspects of the disclosure, independent of the specific ratios of components described herein.

[0120] For purposes of brevity and clarity, each of the features described as an aspect of a given embodiment (in this case, embodiment 1) is also considered a subembodiment of that embodiment, such that any subsequent embodiment that references a preceding embodiment also includes those aspects as separate subembodiments in the latter embodiment.

[0121] In addition to or in addition to the aspects of embodiment 1:

[0122] Embodiment 2.Ln y Ce x M w O z A composition comprising a crystalline mixed oxide having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce.

[0123] In one aspect of this embodiment, Ce is substantially uniformly distributed throughout the crystalline mixed oxide lattice. In another aspect, the crystalline mixed oxide lattice contains, at least in part, a localized concentration of Ce, as described elsewhere herein. The nature and extent of this Ce distribution may be demonstrated by any suitable analytical method, but preferably by one or more of the methods described elsewhere herein.

[0124] In some aspects of this embodiment, each component of the crystalline mixed oxide (i.e., Ce, one or more M elements, Y, and one or more rare earth metals) is present in their fully oxidized valence state. Independently, the M metals may be present in a fully oxidized state, i.e., having a nominal +4 oxidation state. In additional independent aspects of this embodiment, one or more of these metals or elements are present in the composition in a partially oxidized state (i.e., not fully oxidized).

[0125] Embodiment 3. The composition of embodiment 1 or 2, wherein the M element is or comprises Zr or Hf, or a mixture or combination thereof.

[0126] Embodiment 4. The composition of any one of embodiments 1-3, wherein Ln is or comprises Y, La, Nd, Pr, Gd, or Sm. In certain preferred aspects of these embodiments, M is Zr (or Hf) and Ln is La, Nd, Pr, or Y.

[0127] Embodiment 5. The composition according to any one of embodiments 1 to 4, wherein the crystalline mixed oxide is a mesoporous or macroporous aggregate or agglomerate.

[0128] Embodiment 6. The crystalline mixed oxide has a crystallinity of about 10 m 2 g -1 ~about 200m 2 g -1 6. The composition of any one of embodiments 1-5, having a surface area in the range of

[0129] Embodiment 7. The composition according to any one of embodiments 1 to 6, wherein the crystalline mixed oxide has a crystallite size of 100 nm or less.

[0130] Embodiment 8. The composition of any one of embodiments 1-7, wherein the crystalline mixed oxide is in a tetragonal phase, a cubic phase, or a combination thereof. In certain aspects of this embodiment, the crystalline mixed oxide contains less than 10%, less than 5%, less than 3%, less than 2%, less than 1%, or less than 0.5% of pyrochlore phase. In other aspects, the crystalline mixed oxide is substantially free of pyrochlore and / or kappa phase (e.g., no pyrochlore phase is detected by PXRD analysis).

[0131] Embodiment 9. A crystalline mixed oxide exhibiting a PXRD pattern, the ratio of the diffraction line intensities at 2θ=14.5±0.5° and 2θ=29.5±1° (I 14.5 / I 29.5 9. The composition of any one of the preceding embodiments, wherein ) is less than 0.02.

[0132] Embodiment 10. The composition of any one of embodiments 1-9, wherein the crystalline mixed oxide has a Ce-CeCN that is within 20%, within 15%, or within 10% of the theoretical minimum of the corresponding composition assuming perfect Ce distribution.

[0133] Embodiment 11. A method for preparing a crystalline mixed oxide according to any one of embodiments 1 to 10, comprising: (a) subjecting oxide precursors of Ce and one or more of Zr, Hf, Ti, Sn, or Ge, and optionally Y, and / or one or more other rare earth metals excluding Ce, to reducing conditions to form a reduced form of a crystalline mixed oxide; (b) optionally oxidizing the reduced form of the crystalline mixed oxide to form a crystalline mixed oxide.

[0134] Embodiment 12. The method of embodiment 11, wherein oxide precursors of Ce and one or more of Zr, Hf, Ti, Sn, or Ge, and optionally Y, and / or one or more other rare earth metals excluding Ce, are deposited on a high surface carbon support, and then the supported oxide precursors are subjected to carbothermal reduction conditions.

[0135] Embodiment 13. A method of redistributing Ce atoms within an initial Ce-containing mixed oxide composition to provide a final Ce-containing mixed oxide composition having a Ce-Ce CN within 20%, within 15%, or within 10% of the theoretical minimum of the corresponding composition assuming perfect Ce distribution, comprising: The initial Ce-containing mixed oxides are (a) Ce, and optionally Y, and / or one or more other rare earth metals other than Ce; and (b) containing one or more M elements that are Zr, Hf, Ti, Sn, or Ge, or a combination thereof; The method comprises: (a) subjecting the initial mixed oxide to reducing conditions to form a reduced form of the crystalline mixed oxide; (b) oxidizing the reduced form of the crystalline mixed oxide to form the crystalline mixed oxide.

[0136] In such a method, the elemental composition of the Ce-containing mixed oxide before and after treatment is essentially the same, the only difference between the initial and final is the distribution of Ce within the lattice, which is more uniformly distributed after treatment than before (Ce-Ce CN is closer to the theoretical minimum). The degree of uniformity of Ce distribution, and methods for determining the degree of uniformity of this distribution, are described elsewhere herein.

[0137] In some aspects of this embodiment, the Ce-containing mixed oxide composition comprises Ln y Ce x M w O z having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce.

[0138] In certain aspects of this embodiment, the reducing conditions comprise subjecting the initial crystalline mixed oxide to carbothermal reducing conditions. In other aspects of this embodiment, the reducing conditions comprise treating the initial mixed oxide with hydrogen at elevated temperatures.

[0139] Embodiment 14. (a) Gasoline aftertreatment systems, such as TWC or coated gasoline particulate filters (GPFs), (b) Lean NO for diesel aftertreatment systems x trap, (c) PNA, (d) DOC, (e) water gas shift catalyst, (f) hydrocarbon reforming catalyst, including in the case of a steam reforming catalyst and / or a partial oxidation catalyst, and / or (g) H 2 Use of the composition according to any one of embodiments 1 to 10 in a high temperature water splitting catalyst for the production of

[0140] Embodiment 15. The catalytic system is TWC, coated GPF, lean NO for diesel aftertreatment x11. A catalyst system comprising the composition according to any one of embodiments 1 to 10, which is a water gas shift catalyst, a hydrocarbon reforming catalyst, a steam reforming catalyst, a partial oxidation catalyst, and / or a high temperature water splitting catalyst containing trap, Cu, Pt, Au... EXAMPLES

[0141] The following examples are provided to illustrate some of the concepts described within this disclosure. Each example is considered to provide a specific individual embodiment of the composition, preparation method, and use, but should not be considered to limit the more general embodiments described herein. All materials are commercially available and obtained from known sources unless otherwise stated.

[0142] In the following examples, efforts have been made to ensure accuracy with respect to numbers used (e.g., amounts, temperatures, etc.), but some experimental error and deviation should be accounted for. Unless otherwise indicated, temperature is in degrees Celsius, and pressure is at or near atmospheric.

[0143] material All materials are commercially available and were obtained from known sources unless otherwise stated.

[0144] Materials produced in the examples described below and elsewhere herein were, or will be, characterized by one or more of the following analytical methods. PXRD patterns were collected on a Bruker D8 powder diffractometer using CuKα radiation (40-45 kV, 40 mA) between 5° and 100° (2θ) with a step size of 0.04° and 1 second per step. Transmission electron microscopy (TEM) images were acquired on a JEM2800 (scanning) TEM at a voltage of 200 kV. Micropore volume and surface area were measured on a 3Flex surface characterization instrument (Micromeritics) at 77 K using N 2 The measurements were performed using the following method.

[0145] The Strong Reduction Mild Oxidation (SRMO) conditions used in the following examples were as follows: The SR portion of the process was carried out in a flow-through ceramic tube furnace. The powdered support was placed in the bottom of a high-faceted alumina calcination boat with a shallow bed depth. The tube furnace was heated with N 2 After thoroughly flushing with 100% H at a flow rate of approximately 800 mL / min, 2 The furnace was ramped to the set temperature at a rate of 10 °C / min (no holdback). The furnace was then switched to the same 100% H 2 The set temperature was held at ambient for 4 hours, after which the temperature was reset and the furnace was allowed to cool to room temperature without control.

[0146] The MO portion of the process was performed in a static oven. The furnace was ramped up to 500°C at a rate of 10°C / min (no holdback). The furnace was then held at the set temperature for 3 hours, after which the temperature was reset and the furnace was allowed to cool to room temperature without control.

[0147] The OSC was determined in two ways:

[0148] Method 1: A typical OSC experiment uses 10 mL of tracer gas. -1 Use 40 mL of Ar as the carrier gas. -1 0.05 g of sample was oxidized under oxidizing conditions (5% O) using 1000 mL of He. 2 / He 50mL -1 ) and reducing conditions (50 mL of 100% CO -1 The mass spectrometer was used to measure CO over multiple redox cycles. 2 and O 2 Monitor the signal, OSC, CO 2 During the first 300 seconds from the time CO production begins 2 Calculate as area under the curve.

[0149] Method 2: The coated monolithic substrate OSC was used in a gasoline engine with a mass flow rate of 30-70 kg / h. -1The test was performed at a catalyst inlet temperature of 400°C. Lambda was cycled from 1.05 to 0.95 and the OSC reports the change in lambda as a time delay between the AFR sensors before and after the catalyst.

[0150] Example 1: Ce 0.5 Zr 0.5 O 2 The particles were treated separately in air (OSC 1A) and hydrogen under SRMO conditions (OSC 1B) at 900° C. The SRMO treated particles (OSC 1B) had the following properties: SSA: 25m 2 / g; Crystallite size: 12 nm; I 14.5 / I 29.5 : approx. 0.007 Theoretical minimum Ce-O-Ce CN:6.0.

[0151] After treatment in air at 900 °C for 4 h, the Ce-O-Ce CN measured by OSC 1A was found to be 7.8 ± 0.5 (30% of theoretical).

[0152] After treatment in SRMO at 900 °C, the Ce-O-Ce CN measured by OSC 1B was found to be 5.9 ± 0.2 (variation from 0%).

[0153] For OSC 1A and OSC 1B in FIG. 1, OSC method 1 2 As shown in Figure 1, at both 400 and 500 °C, 2 The ability to release was substantially higher for OSC 1B, whose Ce-O-Ce CN was at or near the theoretical minimum, than for OSC 1A, whose Ce-O-Ce CN was further away from this minimum.

[0154] Example 2: La 0.015 Nd 0.045 Ce 0.375 Zr 0.565 O 1.97The particles were treated separately in air (OSC 2A) and hydrogen under SRMO conditions (OSC 2B) at 900° C. The SRMO treated particles (OSC 2B) had the following properties: SSA:47m 2 / g; Crystallite size: 8 nm; I 14.5 / I 29.5 :about 0.000; Theoretical minimum Ce-O-Ce CN: 5.2.

[0155] After treatment in air at 900°C for 4 h, the Ce-O-Ce CN measured by OSC 2A was found to be 6.6 ± 0.4 (within 27% of the theoretical value).

[0156] After treatment in SRMO at 900 °C, the Ce-O-Ce CN measured by OSC 2B was found to be 5.7 ± 0.3 (within 9% of the theoretical value).

[0157] For OSC 2A and OSC 2B, OSC Method 1 2 The corresponding ability to release O is shown in FIG. 2. Again, as shown in FIG. 2, at both 400° C. and 500° C. 2 The ability to release was substantially higher for OSC 2B, whose Ce-O-Ce CN was at or near the theoretical minimum, than for OSC 2A, whose Ce-O-Ce CN was further away from this minimum.

[0158] Example 3: Y 0.063 Ce 0.437 Zr 0.5 O 1.969was prepared as follows: Highly conductive carbon black Ketjen EC300J (5 g) was dispersed in water (400 mL) using a Silverson mixer (4000 rpm, 10 min). The dispersion was then magnetically stirred and the pH adjusted to approximately 9. Yttrium nitrate hexahydrate (2.39 g, 0.00625 mol) was dissolved in water and cerium nitrate solution (1 M, 43.75 mL, 0.04375 mol) and zirconyl nitrate solution (2.2 M, 22.6 mL, 0.05 mol) were added to a total volume of approximately 100 mL. This salt solution was pumped into the carbon slurry at 10 mL / min. The pH was maintained at 9 throughout. Once addition was complete, the slurry was stirred for 30 min and then the carbon supported material was collected by filtration. The sample was washed with water and dried at 105 °C for 16 h.

[0159] The carbon-supported mixed oxide precursors were 2 The material was then calcined in air at 1050° C. for 4 hours to induce ordering without severely sintering the material, and the carbon was then removed by calcining in air at 600° C. for 1 hour.

[0160] Y 0.063 Ce 0.437 Zr 0.5 O 1.969 The particles (obtained above as OSC 3B) had the following properties: SSA:23m 2 / g; Crystallite size: 20 nm; I 14.5 / I 29.5 : approx. 0.016; Theoretical minimum Ce-O-Ce CN: 4.5.

[0161] 100% firing 2 Another batch of material was prepared as above, except that the treatment was carried out in air at 600 °C for 2 h without any treatment, resulting in a carbon-free reference sample as OSC 3A.

[0162] After treatment in air at 600° C. as described in

[0161] , the Ce—O—Ce C N as measured by OSC 3A was found to be 7.5±0.4 (within 67% of the theoretical value).

[0163] As described in

[0159] , H at 1050 °C 2 After subsequent treatment in air at 600°C, the Ce-O-Ce C N measured with an OSC 3B was found to be 5.0±0.3 (within 11% of the theoretical value).

[0164] For OSC 3A and OSC 3B, OSC Method 1 2 The corresponding ability to release O is shown in FIG. 3. Again, as shown in FIG. 3, at both 400° C. and 500° C. 2 The ability to release was substantially higher for samples with Ce-O-Ce CN at or near the theoretical minimum than for samples with Ce-O-Ce CN further away from this minimum.

[0165] Example 4: La 0.015 Nd 0.045 Ce 0.24 Zr 0.705 O 1.98 The particles were treated separately at 900° C. in air (OSC 4A) and hydrogen (SRMO) (OSC 4B).

[0166] The SRMO treated particles (OSC 4B) had the following characteristics: SSA:78m 2 / g; Crystallite size: 8 nm; I 14.5 / I 29.5 :about 0.000; Theoretical minimum Ce-O-Ce CN: 3.6.

[0167] After treatment in air at 900°C for 4 h, the Ce-O-Ce CN measured with an OSC 4A was found to be 4.6 ± 0.5 (within 27% of the theoretical value).

[0168] After treatment in SRMO at 900 °C, the Ce-O-Ce CN measured by OSC 4B was found to be 3.9 ± 0.6 (within 8% of the theoretical value).

[0169] For OSC 4A and OSC 4B, OSC Method 1 2 The corresponding ability to release O is shown in FIG. 4. Again, as shown in FIG. 4, at both 400° C. and 500° C. 2 The ability to release was substantially higher for OSC 4B, which has a Ce-O-Ce CN at or near the theoretical minimum, than for OSC 4A, which has a Ce-O-Ce CN further away from this minimum.

[0170] Example 5: Y 0.125 Ce 0.375 Zr 0.5 O 1.97 was prepared as follows: Highly conductive carbon black Ketjen EC300J (5 g) was dispersed in water (400 mL) using a Silverson mixer (4000 rpm, 10 min). The dispersion was then magnetically stirred and the pH adjusted to approximately 9. Yttrium nitrate hexahydrate (4.79 g, 0.0125 mol) was dissolved in water and cerium nitrate solution (1 M, 37.5 ml, 0.0375 mol) and zirconyl nitrate solution (2.2 M, 22.6 mL, 0.05 mol) were added to bring the total volume to approximately 100 mL. This salt solution was pumped into the carbon slurry at 10 mL / min. The pH was maintained at 9 throughout. Once addition was complete, the slurry was stirred for 30 min and then the carbon support material was collected by filtration. The sample was washed with water and dried at 105 °C for 16 h.

[0171] A portion of the dried carbon-supported mixed oxide precursor was heated with N 2 The powder was calcined in 500° C. for 4 hours at 1050° C. to induce ordering without strongly sintering the material. The carbon was then removed by calcining in air at 600° C. for 1 hour. The resulting particles (OSC 5B) had the following characteristics: SSA:24m 2 / g; Crystallite size: 13.5 nm; I14.5 / I 29.5 : approx. 0.006; Theoretical minimum Ce-O-Ce CN: 4.5.

[0172] Another portion of the dried carbon supported mixed oxide precursor was calcined at 600° C. for 1 h in air without carbon heat treatment to provide reference as OSC 5A.

[0173] After treatment in air at 600° C. as described in

[0172] , the Ce—O—Ce C N measured by OSC 5A was found to be 6.7±0.5 (within 48% of the theoretical value).

[0174] After carbon heat treatment as described in

[0171] , the Ce-O-Ce C N measured by OSC 5B was found to be 4.8±0.4 (within 6% of the theoretical value).

[0175] For OSC 5A and OSC 5B, OSC Method 1 2 The corresponding ability to release O is shown in FIG. 5. Again, as shown in FIG. 5, at both 400° C. and 500° C. 2 The ability to release was substantially higher for OSC 5B, which has a Ce-O-Ce CN at or near the theoretical minimum, than for OSC 5A, which has a Ce-O-Ce CN further away from this minimum.

[0176] Example 6: Y 0.063 Ce 0.375 Zr 0.562 O 1.969was prepared as follows: Highly conductive carbon black Ketjen EC300J (5 g) was dispersed in water (400 mL) using a Silverson mixer (4000 rpm, 10 min). The dispersion was then magnetically stirred and the pH adjusted to approximately 9. Yttrium nitrate hexahydrate (2.39 g, 0.00625 mol) was dissolved in water and cerium nitrate solution (1 M, 37.5 ml, 0.0375 mol) and zirconyl nitrate solution (2.2 M, 25.4 ml, 0.05625 mol) were added to a total volume of approximately 100 mL. This salt solution was pumped into the carbon slurry at 10 mL / min. The pH was maintained at 9 throughout. Once addition was complete, the slurry was stirred for 30 min and then the carbon support material was collected by filtration. The sample was washed with water and dried at 105 °C for 16 h.

[0177] A portion of the dried supported mixed oxide precursor was cooled to 100°C. 2 The powder was calcined in 1050° C. for 4 hours to induce ordering without strongly sintering the material. The carbon was then removed by calcining in air at 600° C. for 1 hour. The resulting particles (OSC 6B) had the following characteristics: SSA:22m 2 / g; Crystallite size: 14.7 nm; I 14.5 / I 29.5 : approx. 0.01; Theoretical minimum Ce-O-Ce CN: 4.5.

[0178] Another portion of the carbon supported mixed oxide precursor was calcined at 600° C. for 1 h in air to provide reference as OSC 6A.

[0179] After treatment in air at 600° C. as described in

[0178] , the Ce—O—Ce C N measured by OSC 6A was found to be 6.9±0.5 (within 53% of the theoretical value).

[0180] After carbon heat treatment as described in

[0177] , the Ce-O-Ce C N measured by OSC 6B was found to be 4.7±0.3 (within 4% of theoretical).

[0181] For OSC 6A and OSC 6B, OSC Method 1 2 The corresponding ability to release O is shown in FIG. 6. Again, as shown in FIG. 6, at both 400° C. and 500° C. 2 The ability to release was substantially higher for OSC 6B, which has a Ce-O-Ce CN at or near the theoretical minimum, than for OSC 6A, which has a Ce-O-Ce CN further away from this minimum.

[0182] Example 7: Single layer three-way catalyst formulations were also prepared using OSC 2A and OSC 2B.

[0183] Catalyst 7A: is a ternary (Pd-Rh) catalyst with a single layer structure. The washcoat consists of Pd and Rh supported on OSC 2A, La-stabilized alumina, and Ba promoter. The washcoat loading is about 3.0 g / in 3 (OSC2A approx. 1.5g / in 3 ) and Pd loading is 63.6g / ft 3 , Rh loading is 6.4g / ft 3 The washcoat was coated (using standard coating procedures) onto a ceramic monolithic substrate, dried at 100° C., and fired at 500° C. for 30 minutes.

[0184] Catalyst 7B: Catalyst 7B was prepared following a similar procedure as catalyst 7A, except that OSC 2B was used instead of OSC 2A.

[0185] For catalyst 7A and catalyst 7B, O by OSC method 2 2 The corresponding ability to release O at 400 °C for all mass flow rates tested is shown in Figure 7. 2 The ability to release was substantially higher for catalyst 7B (containing OSC 2B, whose Ce-O-Ce CN is at or near the theoretical minimum) than for catalyst 7A (containing OSC 2A, whose Ce-O-Ce CN is further away from this minimum).

[0186] Those skilled in the art will recognize that numerous modifications and variations of the present invention are possible in light of these teachings, all of which are contemplated herein.

[0187] The disclosures of each patent, patent application, and publication cited or described in this specification are incorporated herein by reference in their entirety for all purposes, or at least for the context in which they are used herein. (Aspect 1) Ln y Ce x M w O z A composition comprising a crystalline mixed oxide having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce; The composition, wherein the Ce is uniformly distributed throughout the lattice. (Aspect 2) 2. The composition of embodiment 1, wherein M is or comprises Zr or Hf, or a mixture or combination thereof. (Aspect 3) The composition of any one of the preceding claims, wherein Ln is La, Nd, Pr, and / or Y. (Aspect 4) A composition according to any one of the preceding aspects, wherein the crystalline mixed oxide is present as mesoporous or macroporous aggregates or agglomerates. (Aspect 5) The crystalline mixed oxide has a thickness of about 10 m 2 g -1 ~ approx. 100m 2 g -1 The composition of any one of embodiments 1-4, having a surface area in the range of (Aspect 6) 6. The composition according to any one of the preceding aspects, wherein the crystalline mixed oxide has a crystallite size in the range of about 1 nm to about 100 nm. (Aspect 7) Aspects 7. The composition of any one of aspects 1-6, wherein the crystalline mixed oxide is present in a tetragonal phase, a cubic phase, or a combination thereof. (Aspect 8) The crystalline mixed oxide exhibits a powder X-ray diffraction (PXRD) pattern in which the ratio of the diffraction line intensities at 2θ=14.5±0.5° and 2θ=29.5±1° (I 14.5 / I 29.5 8. The composition of any one of the preceding aspects, wherein q is less than 0.02. (Aspect 9) 9. The composition of any one of embodiments 1-8, wherein the crystalline mixed oxide has a Ce-Ce coordination number (CN) that is within 20% of the theoretical minimum for the corresponding composition assuming perfect Ce distribution. (Aspect 10) A method for preparing a crystalline mixed oxide according to any one of aspects 1 to 9, comprising the steps of: (a) subjecting oxide precursors of the Ce, the one or more of Zr, Hf, Ti, Sn, or Ge, and any of the Y, and / or one or more other rare earth metals excluding Ce, to reducing conditions to form a reduced form of the crystalline mixed oxide; (b) optionally oxidizing said reduced form of said crystalline mixed oxide to form said crystalline mixed oxide. (Aspect 11) 11. The method of embodiment 10, wherein the reducing conditions are carbothermal reduction or hydrogen reduction. (Aspect 12) 12. The method of claim 11, wherein the oxide precursors of Ce, one or more of Zr, Hf, Ti, Sn, or Ge, and any of the Y, and / or one or more other rare earth metals excluding Ce are deposited on a high surface carbon support before subjecting the supported oxide precursors to the carbothermal reduction conditions. (Aspect 13) 1. A method for redistributing Ce atoms within an initial Ce-containing mixed oxide composition to provide a final Ce-Ce coordination number (CN) within 20%, within 15%, within 10%, within 5% or less of the theoretical minimum of the corresponding composition assuming perfect Ce distribution, comprising: The initial Ce-containing mixed oxide composition is y Ce x M w O z and having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−xy)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce; The method comprises: (a) subjecting said initial mixed oxide to reducing conditions to form a reduced form of said crystalline mixed oxide; (b) optionally oxidizing said reduced form of said crystalline mixed oxide to form said crystalline mixed oxide. (Aspect 14) (a) gasoline aftertreatment systems such as three-way catalysts (TWC) or (coated) gasoline or diesel particulate filters or soot filters; (b) lean NOx filters for diesel aftertreatment systems x (c) passive NO trap x (d) diesel oxidation catalyst (DOC); (e) water gas shift catalyst; (f) hydrocarbon reforming catalyst, including in the case of a steam reforming catalyst and / or a partial oxidation catalyst; and / or (g) H 2 10. Use of the composition according to any one of embodiments 1 to 9 in a high temperature water splitting catalyst for the production of (Aspect 15) Catalyst systems include TWC, (coated) gasoline particulate filters or diesel particulate filters or soot filters, lean NO for diesel aftertreatment x A catalyst article comprising the composition of any one of aspects 1-9, wherein the composition is a trap, a PNA, a DOC, a water gas shift catalyst, a hydrocarbon reforming catalyst, a steam reforming catalyst, a partial oxidation catalyst, and / or a high temperature water cracking catalyst.

Claims

1. Ln y C x M w O z A composition comprising a crystalline mixed oxide having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−x−y)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce; said crystalline mixed oxide having a Ce-Ce coordination number (CN) that is within 20% of the theoretical minimum Ce-Ce coordination number of the corresponding composition assuming perfect Ce distribution; The crystalline mixed oxide is 10 2 g -1 ~100m 2 g -1 and exists as mesoporous or macroporous aggregates or agglomerates.

2. 2. The composition of claim 1, wherein M is or comprises Zr or Hf, or a mixture or combination thereof.

3. The composition according to claim 1 or 2, wherein Ln is La, Nd, Pr, and / or Y.

4. The composition according to any one of claims 1 to 3, wherein the crystalline mixed oxide has a crystallite size in the range of 1 nm to 100 nm.

5. The composition according to any one of claims 1 to 4, wherein the crystalline mixed oxide is present in a tetragonal phase, a cubic phase, or a combination thereof.

6. The crystalline mixed oxide exhibits a powder X-ray diffraction (PXRD) pattern in which the ratio of the diffraction line intensities at 2θ=14.5±0.5° and 2θ=29.5±1° (I 14.5 / I 29.5 6. The composition according to claim 1, wherein the σ is less than 0.

02.

7. A process for preparing a crystalline mixed oxide according to any one of claims 1 to 6, comprising the steps of: (a) subjecting oxide precursors of the Ce, the one or more of Zr, Hf, Ti, Sn, or Ge, and optionally the Y, and / or one or more other rare earth metals excluding Ce, to reducing conditions to form a reduced form of the crystalline mixed oxide; (b) optionally oxidizing said reduced form of said crystalline mixed oxide to form said crystalline mixed oxide, the reduction conditions are carbothermal reduction conditions, The method further comprising subjecting the supported oxide precursor to the carbothermal reduction conditions after the oxide precursor is deposited on a high surface area carbon support.

8. 1. A method for redistributing Ce atoms within an initial Ce-containing mixed oxide composition to provide a final Ce-Ce coordination number (CN) within 20% of the theoretical minimum Ce-Ce coordination number of a corresponding composition assuming perfect Ce distribution, comprising: The initial Ce-containing mixed oxide composition is y C x M w O z and having a stoichiometry of 0.15≦x≦0.5, y≦0.25, w=(1−x−y)≧0.5, and z=(2x+2w+1.5y), M is Zr, Hf, Ti, Sn, or Ge, or a combination thereof; Ln is one or more rare earth metals other than Y and / or Ce; The method comprises: (a) subjecting the initial Ce-containing mixed oxide composition to reducing conditions to form a reduced form of the final Ce-containing mixed oxide composition; (b) optionally oxidizing the reduced form of the final Ce-containing mixed oxide composition to form the final Ce-containing mixed oxide composition; The final Ce-containing mixed oxide composition is 2 g -1 ~100m 2 g -1 and having a surface area in the range of the reduction conditions are carbothermal reduction conditions, The method of claim 1, further comprising subjecting the initial Ce-containing mixed oxide composition supported to the carbothermal reduction conditions after the initial Ce-containing mixed oxide composition is deposited on a high surface area carbon support.

9. (a) a gasoline aftertreatment system including a three-way catalyst (TWC) or a (coated) gasoline or diesel particulate or soot filter; (b) a lean NOx filter for diesel aftertreatment systems. x trap, (c) passive NO x (d) diesel oxidation catalyst (DOC); (e) water gas shift catalyst; (f) hydrocarbon reforming catalyst, including in the case of a steam reforming catalyst and / or a partial oxidation catalyst; and / or (g) H 2 Use of the composition according to any one of claims 1 to 6 in a high temperature water splitting catalyst for the production of

10. Catalyst systems include TWC, (coated) gasoline particulate filters or diesel particulate filters or soot filters, lean NOx filters for diesel aftertreatment, x 7. A catalyst article comprising the composition of any one of claims 1 to 6 which is a trap, a PNA, a DOC, a water gas shift catalyst, a hydrocarbon reforming catalyst, a steam reforming catalyst, a partial oxidation catalyst, and / or a high temperature water splitting catalyst.

Citation Information

Patent Citations

  • Hydrogen-storing material with low-cerium and production thereof

    CN1817447A

  • Production of multiple oxide having oxygen absorbing-extruding ability

    JP1996103650A

  • Oxygen storage material

    JP2003275580A

  • Ceria-zirconia compound oxide

    JP2003277059A

  • Method of manufacturing nanocarbon material

    JP2004244309A